Understanding arid‐region waterbird community dynamics during lake dry‐downs. Issue 8 (19th August 2021) - Cumming, Graeme S.; Henry, Dominic A. W.; Mutumi, Gregory L.; Ndlovu, Mduduzi
Abstract: The community dynamics of organisms that exhibit multi‐scale responses to habitat change are poorly understood. We quantified changes in species diversity and the functional composition of a waterbird community over two iterations of a repeated transition, the annual drying‐down of arid‐region Lake Ngami, Botswana. We used our data to test three theoretical predictions: simplification of the bird community over time due to a reduction in habitat area and concurrent niche loss; large fluctuations in densities of mobile, opportunistic species; and high variance in predator and prey abundance. Despite temporal variance in species accumulation, we observed no obvious simplification and distinct but consistent groupings of abundance and composition across transitional stages. There were some rapid shifts in functional composition, such as loss of deepwater foragers; winners and losers also occurred within foraging guilds. We conclude that understanding community‐level trends during transitional periods will require stronger theoretical frameworks that more effectively integrate unique species traits and functional groups. For conservation managers, our study offers a cautionary tale of the importance of understanding connectivity, trajectories of change, and the potential for large fluctuations in animal communities independent of management actions during periods of ecological transition.